Utilizing Artificial Intelligence (AI) in Customer’s Purchase Intentions on GrabFood - Ravi, Thevisri; Yusof, Rosmelisa; Koay, Loke Kean; Teoh, Yee Teng; Thin, Mun Yee; Donold, Tiffany Audrey Anak; Jannah, Nur Aini Raudhatul; Mittal, Prachi; Srivastava, Rishabh; Kee, Daisy Mui Hung (AIBPM Publisher, 2024)
Generally, food delivery is a courier service that transfers consumer needs from stores or restaurants to the customer’s doorstep. With the advent of artificial intelligence, people now could order meals and other goods from the convenience of their homes. As such, Grab Holdings, which was founded in 2012 as a taxi-hailing service, is now well-known for providing consumer services including rides (Grab Transport), food deliveries (GrabFood), and package deliveries (Grab Express). The primary purpose of this research is to study on how the artificial intelligence that was utilized in customer’s purchase intentions on Grab Food. The independent variables used to measure this study are instant delivery of foods, estimation of delivery time, customized recommendation on food, interactivity, cashless payment method used and consumer behavior corresponding to the dependent variable of consumer’s intention to use GrabFood. To support the findings of the research, an online survey has been carried out to gather the data needed. This survey was targeted on 100 Malaysian, Indonesian and Indian respondents, from all age groups, ethnicity, and gender. Following, the data gathered were verified using the SPSS software. Based on the study, the result shows that there is a significant correlation between the independent and dependent variables. In addition, instant delivery of foods and customized recommendations on food has a major influence on consumers’ purchase intention on GrabFood Delivery.